Revolution Beyond the Event The afterlives of radical politics - Al-Khalili , Charlotte; Ansari, Narges; lamrani, myriam; Uzel, Kaya (UCL Press, 2023)
Revolution Beyond the Event brings together leading international anthropologists alongside emerging scholars to examine revolutionary legacies from the MENA region, Latin America and the Caribbean. It explores the idea that revolutions have varied afterlives that complicate the assumptions about their duration, pace and progression, and argues that a renewed focus on the temporality of radical politics is essential to our understanding of revolution. Approaching revolution through its relationship to time, the book is a critical intervention into attempts to define revolutions as bounded events that act as sequential transitions from one political system to another. It pursues an ethnographically driven rethinking of the temporal horizons that are at stake in revolutionary processes, arguing that linear views of revolution are inextricably tied to notions of progress and modernity. Through a careful selection of case studies, the book provides a critical perspective on the lived realities of revolutionary afterlives, challenging the liberal humanist assumptions implicit in the 'modern' idea of revolution, and reappraising the political agency of people caught up in revolutionary situations across a variety of ethnographic contexts.